2010
DOI: 10.1117/12.856475
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Imaging Spectrograph (IRIS) for TMT: the atmospheric dispersion corrector

Abstract: We present a conceptual design for the atmospheric dispersion corrector (ADC) for TMT's Infrared Imaging Spectrograph (IRIS). The severe requirements of this ADC are reviewed, as are limitations to observing caused by uncorrectable atmospheric effects. The requirement of residual dispersion less than 1 milliarcsecond can be met with certain glass combinations. The design decisions are discussed and the performance of the design ADC is described. Alternative options and their performance tradeoffs are also pres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…There is one ADC located in each probe arm of the OIWFS, plus two more in IRIS. Drew Phillips has investigated many glass combinations for ADCs in IRIS [3]. One of the best combinations for the IRIS imager is Ohara's S-NPH2 and Spinel, therefore a study was initiated to see if it was a viable material to be used for all ADC's in IRIS.…”
Section: Spinel Adc Glass Studymentioning
confidence: 99%
“…There is one ADC located in each probe arm of the OIWFS, plus two more in IRIS. Drew Phillips has investigated many glass combinations for ADCs in IRIS [3]. One of the best combinations for the IRIS imager is Ohara's S-NPH2 and Spinel, therefore a study was initiated to see if it was a viable material to be used for all ADC's in IRIS.…”
Section: Spinel Adc Glass Studymentioning
confidence: 99%
“…(ADCs) are necessary. 5,6 However, even with an ADC there remain residual errors because 1. even the perfectly built ADC has a wavelength-dependent residual and 2. our knowledge of the atmospheric profiles is incomplete and has uncertainties. Our simulations have shown that the residual dispersion can be on the order of ±15 µas for large zenith angles.…”
Section: Atmosphere [µAs]mentioning
confidence: 99%
“…The peak efficiency for a given order is defined as the measured flux of a monochromatic light source diffracted into that order relative to the total incidence flux. The typical efficiency measurement procedure is as follows: (1) Set up the VPH grating perpendicular to the incidence light beam; (2) rotate the VPH grating to the specific incidence angle; (3) adjust the camera position and angle to measure the diffracted order; (4) change the gain of the attenuator to get a reasonable incidence intensity; (5) take 100 frames of the flux with the best exposure time; (6) block the laser, and take the background of the setup with the same exposure time; (7) repeat the above steps for each order; (8) remove the VPH grating, and measure the pure incidence flux of the laser; and (9) using the flux of the specific diffracted order to divide the total incidence flux of the laser, the efficiency will be calculated. It is important to note that we observed reflected light off the incoming light surface of the VPH grating, which would decrease the total efficiency.…”
Section: Adjustment Process For Measurementmentioning
confidence: 99%